1983
DOI: 10.2151/jmsj1965.61.6_848
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Experiment on the Nocturnal Low Level Jet Over the Kanto Plain

Abstract: The nocturnal low level jet, which appears over the southeastern part of the Kanto Plain, is simulated using a three-dimensional numerical model of the local winds. The results agree well with observations of the horizontal and vertical distribuitons of the jet. The diurnal variation of the jet generally agrees with the observation.However, the amplitude of the diurnal variation is a little smaller and the maximum wind velocity appears a few hours earlier than the observation.From some additional numerical exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Kimura and Arakawa (1983), and Kondo and Mizuno (1990) showed that the wind gained speed over the southeastern part of the Kanto plain for 5-10 m s À1 southwesterly geostrophic flow. The primary factor in this kind of low-level jet formation was the mechanical effect of the mountains in central Japan upon synoptic-scale winds.…”
Section: B Features Of the Wind Fieldmentioning
confidence: 98%
“…Kimura and Arakawa (1983), and Kondo and Mizuno (1990) showed that the wind gained speed over the southeastern part of the Kanto plain for 5-10 m s À1 southwesterly geostrophic flow. The primary factor in this kind of low-level jet formation was the mechanical effect of the mountains in central Japan upon synoptic-scale winds.…”
Section: B Features Of the Wind Fieldmentioning
confidence: 98%
“…The model was developed by Kimura and Arakawa 3) and modified by Kimura and Kuwagata. 4) LCM is a three dimensional, non-hydrostatic, primitive equation model with a terrain following a coordinate system.…”
Section: Appendix 1 Model Description (1) Atmospheric Model (Local Cmentioning
confidence: 99%
“…The governing equations and numerical scheme of the model are the same as those developed by Kikuchi et al (1981), and modified by Kimura and Arakawa (1983). The governing equations are Boussinesq hydrostatic equations written in a terrain-following coordinate system, as follows: The radiation condition given by Orlanski (1976) is adopted for windward and leeward lateral boundaries.…”
Section: Numerical Modelmentioning
confidence: 99%